2006
DOI: 10.1063/1.2159082
|View full text |Cite
|
Sign up to set email alerts
|

Grain-boundary grooving by surface diffusion with asymmetric and strongly anisotropic surface energies

Abstract: Dirichlet extremum problem associated with the asymmetric grain-boundary thermal grooving under the Dirac δtype anisotropic surface stiffness in bicrystal thin solid films Grain-boundary migration controls grain growth, which is important in material processing and synthesis. When a vertical grain boundary ends at a horizontal free surface, a groove forms at the tip to reduce the combined grain-boundary and surface energies. The groove affects the migration of the grain boundary, and its effect must be underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Here, we should mentioned that we have also developed a wetting boundary condition (or interactive-BC) for the electrode-interconnect contact area using the irreversible thermodynamic similar to the GB-TJ formulation. Where, we have found that the cathode area shrinkage or the ridge formation is solely controlled by the surface Gibbs free energies at triple junction, exactly analog to the classical wetting theory, unless one has strong anisotropy, where the torque term might dominate the surface free energies and causes the ridge formation (Min and Wong, 2006).…”
Section: Switch-over Constant Voltage Experiments CVmentioning
confidence: 88%
“…Here, we should mentioned that we have also developed a wetting boundary condition (or interactive-BC) for the electrode-interconnect contact area using the irreversible thermodynamic similar to the GB-TJ formulation. Where, we have found that the cathode area shrinkage or the ridge formation is solely controlled by the surface Gibbs free energies at triple junction, exactly analog to the classical wetting theory, unless one has strong anisotropy, where the torque term might dominate the surface free energies and causes the ridge formation (Min and Wong, 2006).…”
Section: Switch-over Constant Voltage Experiments CVmentioning
confidence: 88%
“…Then, one may combine Eqs. (8) and (9) to obtain the following explicit exact expressions using the definition of the normalized time presented previously…”
Section: Article In Pressmentioning
confidence: 99%
“…Recently, Zhang et al [7] and Xin and Wong [8], prescribed an orientation dependent surface stiffness instead of the surface free energy explicitly in their treatments. Xin and Wong [8] and Min and Wong [9] while utilizing spike function for the faceting in their self-similar transformation theory, discovered very interesting effect of the anisotropy on the Mullins rate constant B measured directly from the Mullins profile function, which shows substantial amount of reduction, where the surface stiffness function shows quasiisotropic behavior, and the surface topography is very smooth (no faceting formation). Recently, Ogurtani [10] has reached exactly the same conclusion for the four-fold symmetry by applying special analysis on the surface Gibbs free energy function adapted from Ramasubramaniam and Shenoy [11] in addition to the verifications by the computer simulation experiments.…”
Section: Introductionmentioning
confidence: 97%
“…(2) is subject to the following boundary conditions. At the contact line x ¼ x c ðyÞ, the height h of the wire surface is zero, the contact angle is in equilibrium, and the mass flux tangent to the wire surface and into the substrate is zero [16,24,23]:…”
Section: Problem Formulationmentioning
confidence: 99%